Standardized Time to Peak in Ischemic and Regular Cerebral Tissue Measured with Perfusion MR Imaging - Našel, Christian; Kronsteiner, Nicole; Schindler, Erwin; Kreuzer, Sören; Gentzsch, Stephan (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Standardized time to peak (stdTTP) enables a quick quantification of time to peak measurements. An stdTTP ≤3.5 seconds is reported to be regular, and evidence suggests that an stdTTP ≥7 seconds indicates critically perfused tissue. We verified this stdTTP in acute ischemia (within the first 6 hours after the onset of symptoms), when perfusion is critical, and after 24–72 hours.METHODS: Combined diffusion-weighted imaging (DWI) and perfusion MR imaging was performed in 20 consecutive patients with acute cerebral ischemia. Distributions of stdTTP ≥7 and ≤3.5 seconds were analyzed in corresponding regions with (ischemic injury) or without (no ischemic injury) substantial hyperintensity on DWI in both hemispheres. Follow-up examinations were available in 11 patients.RESULTS: About 80% of voxels in regions with ischemic injury showed an stdTTP ≥7 seconds. StdTTP of about 80% of voxels was ≤3.5 seconds in regions without ischemic injury. In both conditions, 14% of stdTTP values were between 3.5 and 7 seconds. We found a strong correlation between areas with stdTTP ≥7 seconds and resulting infarct (r2=0.86).CONCLUSION: StdTTP is reciprocal in regions with and without ischemic injury. An stdTTP ≥7 seconds (regular range) is strongly correlated with resulting infarct and reflects critical perfusion with a high probability of ischemic tissue injury in acute ischemia, whereas this is unlikely in regions with stdTTP ≤3.5 seconds (regular range). An stdTTP of 3.5–7 seconds is equivocal concerning ischemic injury and may indicate a tolerable perfusion condition.